Multivariate statistics and water quality index (WQI) approach for water quality assessment in tropical streams and wadeable rivers in Cagayan Valley, Central Visayas, and Caraga (the Philippines) - Velasco, Ashemir B.; Mendoza, Sedney S.; Naling, Chennie S.; Ramos, Myrna T.; Ilano, Anthony S.; Pepito, Cindylyn C.; Magbanua, Francis S. (2025)
We examined the water quality of 36 streams and wadeable rivers across three major regions of the Philippines – Cagayan Valley (Luzon), Central Visayas, and Caraga (Mindanao) – using 10 primary physicochemical and biological parameters identified in the Philippine water quality guidelines. These parameters included temperature, dissolved oxygen (DO), pH, biological oxygen demand (BOD), total suspended solids (TSS), nitrate, phosphate, chloride, fecal coliform (FC), and color. Results showed significant spatial variability in water quality across regions, with all parameters except color differing significantly (p < 0.05). Principal component analysis (PCA)revealed that BOD, FC, nitrate, phosphate, and chloride were the most influential indicators of water quality variation – highlighting the combined impact of domestic wastewater, agricultural runoff, and insufficient sanitation infrastructure. Strong correlations were found between BOD and FC, suggesting common pollution sources. The weighted arithmetic water quality index (WQI) was used to classify each site. Only 11% of streams and rivers were rated as having good water quality, whereas 39% were classified as poor and 50% as unsuitable for drinking. Notably, the majority of degraded sites were located in the Central Visayas region. This study demonstrates the utility of combining the WQI and multivariate statistical tools to simplify complex datasets and prioritize indicators for more cost-effective and responsive monitoring. The findings underscore the urgency of expanding water quality surveillance, especially in vulnerable or unclassified river systems where monitoring is often limited. Equally important is improving wastewater management in rural and peri-urban areas through localized treatment facilities and more consistent enforcement of pollution controls under the Philippine Clean Water Act. Developing a national WQI framework, guided by PCA-prioritized indicators, can strengthen evidence-based decision-making for river health management in the Philippines.
Keywords: Water quality; Quality of Water; Water pollution; Water - Pollution